CHARACTERISTIC OF NASOPHARYNGEAL CARSINOMA IN ACEH 2016-2017 - Benny Kurnia; Reno Keumalazia Kamarlis; Fera Kamila Kamal (TALENTA PUBLISHER, 2019)
Introduction Nasopharyngeal carcinoma is among five major malignancies in Indonesia and the primary malignant tumor in men. Among all head and neck (H&N) cancers, nasopharyngeal carcinoma (NPC) is endemic in certain regions of the world, especially in Southeast Asia, and has a poor prognosis. In Indonesia, the recorded mean prevalence is 13 000 yearly new NPC cases, but otherwise little is documented on NPC in Indonesia. Objectives We collected all cases of nasopharyngeal carcinoma diagnosed by histopathological examination during the period of 2016-2017 from archives of the registry in the Ear, Nose, and Throat department and Patologi Anatomy laboratory Dr. Zainoel Abidin General Hospital. We did this research to presenting the basic data of NPC in Aceh according to gender, age, geographic site and WHO histopathology criteria. Method All the data we counted by using Microsoft Excel 2016 by grouping it according to the variable that we want to grade. We made it into a table and graphic presentation to explain each item of the variable. Result Here, in Aceh, we reported 46 cases in the year 2016 and 26 cases in the year 2017, a total of 72 patients during 2 years. We studied NPC incidence in Aceh among all H&N cancer cases focusing on age, gender, the ethnic background, and the disease histopathology. In this study population, from a total of 72 patient we found 44 male (61.1%) and 28 female (38.9%), with a male to female ratio is 1.57:1. According to the geographic site, NPC in Aceh was the most endemic in the Banda Aceh population (15.3%) followed by Southwest Aceh (12.5%) as a second one. From the age range, NPC most frequent to affect patients at the age range 41-60 years (44.44%), besides that we found 8 (11.11%) cases NPC in Aceh at the age 0- 20 years with 13 years old patient was the younger one. Here, we found that Undifferentiated NPC is the most frequent histological type (44.4%). We continued the study by analyzed NPC patient according to WHO criteria, type I WHO most frequent from the Great Aceh. Type II and Type III WHO we found most frequent from Banda Aceh. Conclusion: Our data NPC incidence did not differ significantly among the literature. Mostly NPC patients over the world at the old adult age, even all of the age range can be affected by NPC. There are similar histopathological features results here compare to the Southeast Asian country.